Patients, Doctors and Healers Medical Worlds among the Mapuche in Southern Chile - Kristensen, Dorthe Brogård; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
Recognizing the interplay between biomedicine and indigenous medicine among the Mapuche in Southern Chile, this book explores notions of culture and personhood through the bodily experiences and medical choices of patients. Through case studies of patients in the context of medical pluralism, Kristensen argues that medical practices are powerful social symbol indicative of overarching socio-political processes. As certain types of extreme and violent experiences-known as olvidos-lack a framework that allows them to be expressed openly, they therefore surface as symptoms of an illness, often with no apparent organic pathology. In these contexts, indigenous medicine, thanks to its sensitivity to socio-political contexts, provides a space for articulation and management of collective experiences and suffering among patients in Southern Chile.
1. Illness Stories, Medical Choices and Socio-Political Process -- 2. The History, Culture and Politics of Chile -- 3. Complex Illnesses and Complementary Cures -- 4. Indigenous Disease Categories, Medical Dialogues and Social Positions -- 5. Being Mapuche in Modern Chile: Illness Experiences, Medical Choices and Social Positions -- 6. Uncanny Memories, Violence and Indigenous Medicine -- 7. The Shaman, the Virgin and the Taxation Authorities -- 8. Conclusion: The Control of Medicine, the Control of Bodies.
Keywords: Medical anthropology; Ethnology; Political sociology; Alternative medicine; Spirituality; Phenomenology .; Medical Anthropology; Sociocultural Anthropology; Political Sociology; Complementary and Alternative Medicine; Spirituality; Phenomenology